Performance evaluation of a high flow rate annular linear induction pump using a simple equivalent circuit model taking into account dynamic end effects - Emmanuel Lo Pinto; Pascal Defrasne; Frédéric Rey; Mathilde Talluau; Ciaran Verdelli (Annals of Nuclear Energy, 2023)

On the supra-linearity of the relationship between air pollution, mortality and hospital admission in 18 French cities - Vérène Wagner; Mathilde Pascal; Magali Corso; Anna Alari; Tarik Benmarhnia; Alain Le Tertre (International Archives of Occupational and Environmental Health, 2023)

A point mutation and large deletion at the candidate avirulence locus AvrMlp7 in the poplar rust fungus correlate with poplar RMlp7 resistance breakdown - Clémentine Louet; Méline Saubin; Axelle Andrieux; Antoine Persoons; Mathilde Gorse; Jérémy Pétrowski; Bénédicte Fabre; Stéphane De Mita; Sébastien Duplessis; Pascal Frey; Fabien Halkett (Molecular Ecology, 2023)
The deployment of plant varieties carrying resistance genes ( R ) exerts strong selection pressure on pathogen populations. Rapidly evolving avirulence genes ( Avr ) allow pathogens to escape R ‐mediated plant immunity through a variety of mechanisms, leading to virulence. The poplar rust fungus Melampsora larici ‐ populina is a damaging pathogen of poplars in Europe. It underwent a major adaptive event in 1994, with the breakdown of the poplar RMlp7 resistance gene. Population genomics studies identified a locus in the genome of M . larici ‐ populina that probably corresponds to the candidate avirulence gene AvrMlp7 . Here, to further characterize this effector, we used a population genetics approach on a comprehensive set of 281 individuals recovered throughout a 28‐year period encompassing the resistance breakdown event. Using two dedicated molecular tools, genotyping at the candidate locus highlighted two different alterations of a predominant allele found mainly before the resistance breakdown: a nonsynonymous mutation and a complete deletion of this locus. This results in six diploid genotypes: three genotypes related to the avirulent phenotype and three related to the virulent phenotype. The temporal survey of the candidate locus revealed that both alterations were found in association during the resistance breakdown event. They pre‐existed before the breakdown in a heterozygous state with the predominant allele cited above. Altogether, these results suggest that the association of both alterations at the candidate locus AvrMlp7 drove the poplar rust adaptation to RMlp7 ‐mediated immunity. This study demonstrates for the first time a case of adaptation from standing genetic variation in rust fungi during a qualitative resistance breakdown.

Changes in the temperature-mortality relationship in France: Limited evidence of adaptation to a new climate - Mathilde Pascal; Vérène Wagner; Magali Corso (International Journal of Biometeorology, 2023)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Low vulnerability of the Mediterranean antipatharian Antipathella subpinnata (Ellis & Solander, 1786) to ocean warming - Godefroid Mathilde; Zeimes Tom; Bramanti Lorenzo; Romans Pascal; Bo Marzia; Toma Margherita; Danis Bruno; Dubois Philippe; Guillaumot Charlène (Ecological Modelling, 2023)